Blunt abdominal trauma: the experience in rural India and review of literature - Ahmed, Mohd Hamid Shafique; Tamgadge, Lalit Vishwanath; Gurav, Prakash D.; Dalavi, Santosh B.; Bankar, Sanket; Parmar, Ritesh (International Journal of Research in Medical Sciences, 2019)
Background: Blunt Abdominal trauma is one of the most common injuries caused due to road traffic accidents. The rapid increase in number of motor vehicles and its aftermath has caused rapid increase in number of victims due to blunt abdominal trauma. As the care of patients with blunt abdominal injuries is largely a surgical responsibility and abdominal injuries involving major hemorrhage from solid viscera constitute surgical emergencies. Abdominal blunt traumas represent a real diagnostic and therapeutic challenge to even a most experienced surgeon, thereby representing importance of its study. Early diagnosis and effective management help in decreasing mortality in blunt abdominal trauma. Methods: Prospective study of 50 patients admitted to the institute with history of Blunt Abdominal Trauma. After initial resuscitation of the patients, thorough assessments for injuries were carried out in all the patients. Documentation of patients, which included identification, history, clinical findings, diagnostic test, operative findings, operative procedures and complications during the stay in the hospital were all recorded on a Performa specially prepared. The management was decided depending upon history, clinical examination and investigations. Results: Males were predominantly affected, and most cases were between the age group of 21-40 years (76%). Majority of the patients (90%) presented with the complaint of abdominal pain followed by abdominal distension (56%). 36(60%) patients were managed conservatively while operative interventions were required in 24(40%) patients. The common surgeries performed in the patients included splenectomy, primary closure of perforation and resection and anastomosis of bowel. Majority of the patients (80%) were discharged within 20 days of admission. The mortality in present study was 13.3%. Conclusions: Blunt Abdominal Trauma is one of the important causes of morbidity and mortality in young adults. Immediate resuscitative measures, management of associated injuries and appropriate operative intervention are important parts of management of such cases.